2015
DOI: 10.1111/cobi.12558
|View full text |Cite
|
Sign up to set email alerts
|

Credibility and advocacy in conservation science

Abstract: Conservation policy sits at the nexus of natural science and politics. On the one hand, conservation scientists strive to maintain scientific credibility by emphasizing that their research findings are the result of disinterested observations of reality. On the other hand, conservation scientists are committed to conservation even if they do not advocate a particular policy. The professional conservation literature offers guidance on negotiating the relationship between scientific objectivity and political adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 56 publications
(85 reference statements)
1
34
0
Order By: Relevance
“…The introductory or concluding paragraph was used if the publication did not have an abstract. Building on Horton et al (2016), we used 2 categories (credibility and risk) and 7 subcategories (credibility-expertise, goodwill, trustworthiness, and risk-biodiversity, scientific credibility, sustainability, trust). We defined credibility-expertise as conservation scientists' specialized knowledge, credibility-goodwill as conservation biologists' care for natural resources and society, and credibilitytrustworthiness as conservation biologists' integrity.…”
Section: Methodsmentioning
confidence: 99%
“…The introductory or concluding paragraph was used if the publication did not have an abstract. Building on Horton et al (2016), we used 2 categories (credibility and risk) and 7 subcategories (credibility-expertise, goodwill, trustworthiness, and risk-biodiversity, scientific credibility, sustainability, trust). We defined credibility-expertise as conservation scientists' specialized knowledge, credibility-goodwill as conservation biologists' care for natural resources and society, and credibilitytrustworthiness as conservation biologists' integrity.…”
Section: Methodsmentioning
confidence: 99%
“…Frewer, Scholderer, and Bredahl (2003) have also found that trust can mediate attitudes toward new scientific technologies. Expertise refers to "competence" (McCroskey & Teven, 1999), "specialized knowledge" (Horton et al, 2016), and the degree to which a source is perceived as making correct assertions (Hansen, Holm, Frewer, Robinson, & Sandøe 2003;Hovland & Weiss, 1951-1952. Scientists are ascribed particular expertise because they communicate from what Goodnight (2012) has called the "technical sphere," or discursive context that privileges particular norms, styles of engagement, and argumentative appeals, a position that affords them legitimacy and cultural authority (Gauchat, 2011;O'Brien, 2012).…”
Section: Source Credibilitymentioning
confidence: 99%
“…Goodwill, the third-and perhaps "lost" (McCroskey & Teven, 1999)-dimension of source credibility has received considerably less attention. Rooted in the Aristotelian concept of ethos, goodwill represents the degree to which a speaker is perceived as caring, demonstrated through empathy in direct interactions with others (Horton et al, 2016;Hovland et al, 1953;Teven, 2008). Thus, goodwill is "a meaningful predictor of believability and likeableness" (McCroskey & Teven, 1999).…”
Section: Source Credibilitymentioning
confidence: 99%
See 2 more Smart Citations